ANALYSIS OF THE PERFORMANCE EFFICIENCY OF THE ELECTRIC SHUTTLE BUS DRIVE SYSTEM RESULTING FROM CONVERSION - Rahma Yunia Adini; Ramdhani; Sriyono; Tatang Permana (Universitas Majalengka, 2025)
This research aims to analyze the performance of the electric drive system in electric shuttle busses converted from internal combustion engine (ICE) vehicles to battery-based electric vehicles. The focus of the study is directed toward evaluating the technical characteristics of the electric motor, battery capacity and endurance, range estimation, power requirements, and the efficiency of the vehicle's drive system. The research method used is a quantitative descriptive method, literature study, and mathematical modeling based on the vehicle's technical specifications, including vehicle mass, battery capacity, power and torque of the electric motor, as well as vehicle resistance parameters such as rolling resistance and aerodynamic drag. The analysis results show that 2 lithium iron phosphate (LiFePO₄) batteries with a capacity of 15.84 kWh can support an operating time of approximately 6.46 hours with an estimated range of 323 km at a speed of 50 km/h. The motor power calculation shows that the electric motor has a maximum power of 96.33 kW, while the actual power requirement of the vehicle on flat roads is only about 4.8 kW. These results indicate that the electric drive system has sufficient power reserves and is technically feasible for use in the converted electric shuttle bus